(untitled) (Medicine Today, 2025)
Introduction with Objective: Portal vein diameter is important in portal hypertension. So this study was designed to see portal vein diameter among healthy adult. Materials and Methods: Consecutive healthy (nondiabetic, normotensive without clinical, biochemical and sonological evidence of liver disease) were enrolled. Portal vein diameter in resting, inspiratory and expiratory phases were recorded. Average of data of resting, inspiratory and expiratory diameters were calculated. And average of all three diameters of each person were taken as mean portal vein diameter. Relation of portal vein diameters with age, sex, BMI and abdominal circumference were calculated using SPSS version 20. Result: Total 237 (male 135; 57.0% and female 102; 43.0%, age ranging from 18 years to 93 years, mean 38.19) were enrolled. The mean portal vein diameter was 8.81 mm ranging from 6.1 mm to 13 mm for both sexes. Portal vein diameter was significantly higher among males (mean 9.06 mm vs 8.47mm; P=0.003). Within females portal vein diameter varied significantly with BMI. Conclusion: The mean portal vein diameter in our study was 8.81 mm (ranging from 5 mm to 13 mm. So higher diameter may give suspicion for raied portal vein pressure. Medicine Today 2025, Vol.37 (2): 171-173